What can instructors focus on when improving undergraduate science experiments? Supporting a cross- disciplinary approach - Yeung, Alexandra; Cornish, S.; Kable, S.; Sharma, M. (2019)
For nearly two decades, the Australian national project Advancing Science and Engineering through Laboratory Learning (ASELL), has been using an evidence based approach to improve undergraduate experiments. This paper presents the ASELL Students Laboratory Experience (ASLE) survey, administered to 2691 students in five disciplines: biochemistry, biology, chemistry, physics, and pharmacology. The 14 item survey probes students' perceptions of an experiment, practical or fieldwork. An exploratory factor analysis extracted two factors, 'experiment-based motivators' and 'course-level resources', and both factors correlate well with 'overall' learning experiences. Each survey item was also compared to the 'overall' learning experiences of the experiment, revealing the most critical elements of each experiment. The implications of this analysis, for practitioners is that the survey items in the 'course-level resources' taper off indicating that after an optimum value, further investment in these aspects do not necessarily influence student perceptions of their learning experiences. On the other hand, the survey items in the 'experiment-based motivators' behave differently in that they do not taper off indicating that further investment can influence experiences. How these factors relate to the overall experience suggest they correspond to the well-known two-factor theory of motivation.